2021
DOI: 10.1002/clc.23725
|View full text |Cite
|
Sign up to set email alerts
|

Lipid goal attainment in post‐acute coronary syndrome patients in China: Results from the 6‐month real‐world dyslipidemia international study II

Abstract: Background: Dyslipidemia International Study II (DYSIS II)-China was conducted to determine the low-density lipoprotein cholesterol (LDL-C) goal (<1.8 mmol/L) attainment rate in patients with post-acute coronary syndrome (ACS). Hypothesis: Compliance with treatment guideline recommendations improves the LDL-C goal attainment rate in post-ACS patients.Methods: This multicenter prospective observational study conducted at 28 tertiary hospitals determined the LDL-C goal attainment rates at admission and 6-month f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Despite the body of evidence from basic scientific investigations, longitudinal cohorts, prospective randomized clinical trials of pharmacological interventions, and various meta-analyses, the majority of high- and very-high-risk patients remain undertreated. 4–6 More aggressive LDL-C reduction correlates with lower risk of myocardial infarction, ischemic stroke, need for coronary and peripheral revascularization, and death and lower rates of progression of atherosclerotic disease. 7,8 Given these observations, it is important to identify and ameliorate barriers to appropriate care to best serve the needs of patients at risk of ASCVD.…”
mentioning
confidence: 99%
“…Despite the body of evidence from basic scientific investigations, longitudinal cohorts, prospective randomized clinical trials of pharmacological interventions, and various meta-analyses, the majority of high- and very-high-risk patients remain undertreated. 4–6 More aggressive LDL-C reduction correlates with lower risk of myocardial infarction, ischemic stroke, need for coronary and peripheral revascularization, and death and lower rates of progression of atherosclerotic disease. 7,8 Given these observations, it is important to identify and ameliorate barriers to appropriate care to best serve the needs of patients at risk of ASCVD.…”
mentioning
confidence: 99%
“…The medical records of the DM patients enrolled in this study were extracted from the DYSIS II-China study database. The DYSIS II-China study was a multicenter prospective observational study conducted between September 2017 and May 2019, which aimed to assess LDL-C goal attainment in Chinese patients with ACS [ 11 ]. The inclusion criteria were as follows: (1) age ≥ 18 years old, (2) written informed consent was obtained, (3) hospitalized for ACS, (4) complete lipid profile within 24 h after admission, (5) on LLT for ≥ 3 months at the time of enrollment, or not at all on LLT.…”
Section: Methodsmentioning
confidence: 99%
“…Further analyses based on the global DYSIS II study demonstrated that only 11.3% of type 2 DM patients hospitalized for ACS achieved the LDL-C goal of < 1.4 mmol/L at admission, and this attainment rate was improved to 22.5% at the 4-month follow-up [ 10 ]. For Chinese patients, the DYSIS II-China study aimed to assess the LDL-C goal (< 1.8 mmol/L) attainment rate in post-ACS patients including DM patients, who accounted for 28.6% of the whole population [ 11 ]. Hence, in the present analysis of the DYSIS II-China study, we attempted to specifically investigate the LLT patterns and LDL-C goal attainment of < 1.4 mmol/L at baseline and at 6 months post-ACS in DM patients.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results from "The IMPROVE-IT" study, the target LDL-C < 1.8 mmol/L and < 1.4 mmol/L was achieved with high-intensity simvastatin monotherapy and combination therapy of high-dose simvastatin and ezetimibe respectively. The ODYSSEY Outcomes study showed that the LDL-C level in ACS patients treated with alirocumab was reduced to 1.38 mmol/L [ 20 , 21 ]. The Dyslipidaemia International Study II (DYSIS II) based on data from 10,661 patients from 18 countries demonstrated a significant increase in the percentage of patients followed up after ACS from 65.2% to 95.6%; 93.4% of patients were on statin monotherapy only.…”
Section: Reviewmentioning
confidence: 99%